Minds behind the brain : a history of the pioneers and their discoveries - Finger, Stanley (2000)
Traza el estudio del cerebro de los antiguos egipcios, a través del mundo clásico de Hipócrates, los tiempos de Descartes, y la era de Broca, para los investigadores modernos, como Sperry, y examina sus fuentes y herramientas.
Introduction: a voyage across time -- An ancient Egyptian physician: the dawn of neurology -- Hippocrates: the brain as the organ of mind -- Galen: the birth of experimentation -- Andreas Vesalius: the new "human" neuroanatomy -- Rene Descartes: the mind-body problem -- Thomas Willis: the functional organization of the brain -- Luigi Galvani: electricity and the nerves -- Franz Joseph Gall: the cerebral organs of mind -- Paul Broca: cortical localization and cerebral dominace -- David Ferrier and Eduard Hitzig: the experimentalists map the cerebral cortex -- Jean-Martin Charcot: clinical neurology comes of age -- Santiago Ramon y Cajal: from nerve nets to neuron doctrine -- Charles Scott Sherrington: the integrated nervous system -- Edgar D. Adrain: coding the nervous system -- Otto Loewi and Henry Dale: the discovery of neurotransmitters -- Roger W. Sperry and Rita Levi-Montalcini: from neural growth to "split brains" -- Pioneers and discoveries in the brain sciences.
Keywords: CEREBRO -- INVESTIGACION -- HISTORIA; NEUROCIENCIAS -- HISTORIA